Minimum variance linear receivers for multi-access interference rejection in space-time block coded MIMO communication systems - Shahbazpanahi, S.; Beheshti, M.; Gershman, A.B.; Gharavi-Alkhansari, M.; Wong, K.M. (2003 37th Asilomar Conference on Signals, Systems and Computers, 2003)
The problem of joint space-time decoding and multi-access interference (MAI) rejection in multi-user multiple-input multiple-output (MlMO) wireless communication systems is considered. We address the case when both the receiver and multiple transmitters are equipped with multiple antennas and when space-time block codes (STBCs) are used to send the data simultaneously from each transmitter to the receiver. A new linear receiver structure is developed to decode the data sent from the transmitter-of-interest while rejecting MAI, self-interference and noise. The proposed receivers are designed by minimizing the output power subject to constraints which zero-force self-interference and/or preserve a unity gain for all symbols of the transmitter-of-interest. Simulation results show that in multi-access scenarios, the proposed techniques have substantially lower symbol error rates as compared to the matched filter (MF) receiver which is equivalent to the maximum likelihood (ML) space-time decoder in the point-to-point MIMO communication case.